Numerical investigation of stiffened plate girders under multiple patch loading - Ali, Mubashir; Rajeevan, B. (Journal of Structural Engineering, 2024)
Plate girders are widely used in long-span applications. Patch loading is one of the most typical loads a plate girder issubjected to. These partially distributed loads traverse along the span of a plate girder’s top or bottom flange. Lengthand number of patch loads are the governing factors that decide the system’s patch load capacity. The present studyconducted a numerical investigation using finite element models developed in ABAQUS®. The existing experimentalresults in the literature were used to develop the numerical models and then validated against the results obtainedfrom experiments. The effect of plate girders subjected to multiple patch loading was also evaluated and compared inthis study. The spacing of patch loads allows for the distribution of the load to a larger area and influences the patchload capacity. The effect of multiple patch loads on longitudinally stiffened and unstiffened girders was evaluated. Theoptimum position of longitudinal stiffeners was found for girders subjected to multiple patch loading. The effect ofdifferent stiffener arrangements was assessed to find the most effective arrangement for efficiently resisting patch loads.Stiffeners placed close to the loaded flange were found beneficial in patch load resistance.